2004
DOI: 10.1002/nau.20035
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia inhibits human bladder smooth muscle cell proliferation: A potential mechanism of bladder dysfunction

Abstract: In an in vitro human detrusor cell culture model, cells demonstrate a resistance to hypoxia-induced apoptosis but proliferation is inhibited. We suggest that the anti-proliferative effects of hypoxia may limit the ability of detrusor cells to respond to, and compensate for, alterations in their environment contributing to bladder dysfunction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 18 publications
0
32
0
1
Order By: Relevance
“…The response of human detrusor muscle to hypoxic insult was investigated in an in vitro cell culture model [9]. Those authors reported a time-dependent increase in HIF-1 α expression (up to 72 h) with a doubling of vascular endothelial growth factor (VEGF), while spontaneous cell apoptosis and viability were not influenced.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The response of human detrusor muscle to hypoxic insult was investigated in an in vitro cell culture model [9]. Those authors reported a time-dependent increase in HIF-1 α expression (up to 72 h) with a doubling of vascular endothelial growth factor (VEGF), while spontaneous cell apoptosis and viability were not influenced.…”
Section: Discussionmentioning
confidence: 99%
“…LUTS were classified according to the IPSS as minimal (score 0-7), moderate (8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19) and severe ( > 20). The duration of LUTS was also recorded .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…There are some data to support the importance of hypoxia in LUTS, 85 although there is debate regarding potential mechanisms. 86 It is also reasonable to generalize the concept to incorporate other forms of vascular compromise that may contribute to hypoxia or other local perfusion-induced anatomical or functional problems. For instance, measures of perfusion have shown vascular changes in prostate and corpora cavernosa, suggesting disease common to both sites.…”
Section: Pelvic Atherosclerosismentioning
confidence: 99%